Case report: Dupilumab for the treatment of bullous pemphigoid. Issue 7 (13th May 2022) - Wang, Mengxin; Wang, Juan; Shi, Bingjun
Abstract: Bullous pemphigoid (BP) is an inflammatory subepidermal blistering disease with rising prevalence in the elderly individuals. Cytokines associated with Th2‐type immune response play an important role in the pathogenesis of BP. The traditional glucocorticoids and immunosuppressants are recommended as first‐line drugs, but their therapeutic use is limited by numerous adverse effects. Dupilumab is a humanized monoclonal antibody that targets IL‐4 and IL‐13. It has recently been approved for the treatment of atopic dermatitis and may be an attractive therapeutic option for BP as well. Herein, we report two cases of BP treated with dupilumab. It was effective and well tolerated. Further research is needed to assess the efficacy of dupilumab in BP patients.